The Role of Intersubjectivity Philosophy in the Disputive Group Relationship Era - Alvian Apriano; Naupal Asnawi; Fristian Hadinata (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
In contemporary Indonesian society, religious groups face critical challenges in maintaining cohesive relationships amidst increasing individualism and political engagement opportunities. The tendency toward individuation—where members prioritize personal interests over collective goals—threatens to erode the foundational bonds of voluntarism and shared commitment that characterize these communities. This research aims to explore the concept of intersubjectivity, particularly Gabriel Marcel's philosophy of co-esse (being-with), as a restorative framework for addressing disputive relationships within religious groups, while synthesizing insights from Edmund Husserl's empathy and Martin Buber's dialogical philosophy. The study employs a qualitative method based on literature review with a descriptive-analytical philosophical-theological approach, utilizing hermeneutic interpretation and thematic content analysis of primary philosophical texts and contemporary empirical studies on Indonesian religious group dynamics. The analysis reveals that Husserlian empathy provides the foundation for recognizing shared reality through analogical apperception, Buberian dialogue distinguishes authentic I–Thou encounters from instrumental I–It relationships, and Marcelian intersubjectivity offers the most comprehensive framework by grounding human existence in relational ontology rather than isolated individualism. The research concludes that Marcel's intersubjectivity transforms relationships from strategic utility to existential co-existence, providing both diagnostic clarity and normative guidance for religious communities navigating political complexities. The implications extend theoretically by bridging existential phenomenology with empirical social analysis, practically by offering ethical frameworks for group governance and leadership formation, and policy-wise by suggesting governmental approaches that respect communal character rather than incentivizing instrumental participation, thereby strengthening both religious group integrity and broader social cohesion.